Assessment of Physiology and Quality Performances of Cut Foliage Plant (Asparagus plumosus) under Coloured Shade Nets - Chowdhuri, Tapas Kumar; Sadhukhan, Raghunath; Ghosh, Tushar (International Journal of Bio-resource and Stress Management, 2021)
The investigations were carried out during 2016–17 and 2017–18 under three different coloured shade nets (white, green and red) along with the controlled environment (open condition) at Horticultural Research Station, Mondouri, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India to study the production behavior of Asparagus plumosus, India. The experiments were arranged in Complete Randomized Design (CRD) with four replications and maintained in pots. Similar management practices were followed for all the treatments throughout the growing period. The pooled data of two years revealed that plants grown under the green shade net showed significant improvement in all the vegetative parameters i.e. plant height (109.6 cm), plant spread (70.67 cm), leaf length (33.35 cm), leaf breadth (22.00 cm) and petiole girth (0.80 cm), whereas lowest data observed in the plants maintained without any shade net. The leaf production was also better in the plants raised under green shade net than other treatments. The highest number of leaves per plant and leaf longevity was found in green shade net treatment. The leaf production interval was remarkably lowest in the plants grown under green shade net. The leaf quality was better under green shade net in terms of colour intensity, vase life and chlorophyll content. The green shade net gave overall better performance regarding both physiological and quality parameters and can be suitable for commercial cultivation.